Pendampingan Pembelajaran Al-Qur’an di TPQ: Upaya Peningkatan Pemahaman Melalui Inovasi Metode Mengajar - Huda, Nurul; Fitrianingsih, Endah; Swari, Maulida Fuji Anjas; Isnaini, Isnaini (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2026)
Quranic learning at the Quranic Education Center (TPQ) plays a crucial role in shaping children's character and spirituality from an early age. However, in practice, various problems remain, such as students' poor understanding of makhraj and tajwid, weak learning motivation, and a lack of variety in teaching methods used by Quranic teachers at the TPQ. The primary issue of this community service program is the lack of innovation in learning methods, which results in suboptimal learning outcomes for children. The community service program employed a Participatory Action Research (PAR) approach, involving teachers, students, and parents in problem identification, method planning, implementation, and evaluation. Teachers became more confident in teaching, students became more active and motivated, and parents participated in supporting their children's learning at home. This community service program recommends that TPQs adopt a more creative and collaborative learning approach as a long-term strategy to improve the quality of Quranic education.   Keywords: Mentoring, Learning, Innovation, and Methods